2019
DOI: 10.1159/000496631
|View full text |Cite
|
Sign up to set email alerts
|

Predilution On-Line Hemodiafiltration Improves Albumin Redox in Maintenance Hemodialysis Patients

Abstract: Background/Aim: In this study, we compared the dialysis efficiency, oxidative stress, and nutritional conditions between predilution on-line hemodiafiltration (pre-OL-HDF) and conventional hemodialysis (HD) using a super-flux dialyzer (CHD). Method: This was a crossover study of 38 maintenance HD patients. All patients were treated with CHD for the first 4 months (1st CHD period), then were switched to pre-OL-HDF for 4 months (pre-OL-HDF period), and were returned to CHD for the next 4 months (2nd CHD period).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Nakatani et al reported that age, anemia, and eGFR were signi cantly and independently associated with HNA in pre-dialysis CKD patients 15 . Studies reported that hemodialysis may remove uremic toxins and ameliorate the redox status of albumin by decreasing levels of HNA 30,31 . In a community dwelling-based survey, the results demonstrated an inverse association between renal function and HNA 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakatani et al reported that age, anemia, and eGFR were signi cantly and independently associated with HNA in pre-dialysis CKD patients 15 . Studies reported that hemodialysis may remove uremic toxins and ameliorate the redox status of albumin by decreasing levels of HNA 30,31 . In a community dwelling-based survey, the results demonstrated an inverse association between renal function and HNA 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these reports and the present ndings suggest that HNA is indeed signi cantly associated with the pro-atherosclerotic process.An elevated HNA level was reported to be pro-atherosclerotic in previous reports. Fujii et al investigated the associations between the redox status of serum albumin and the carotid intima-media thickness (IMT) in a total of 281 residents 30 . The results showed that a higher HNA level was positively correlated with a thicker carotid intima-media thickness (IMT) 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is reported to be increased in patients with CKD and HD patients [ 26 , 27 ]. As oxidative stress is associated with both increased cardiovascular and peripheral vascular disease [ 8 ], we measured ischaemia modified albumin and calculated the IMAR to allow comparison between patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our results would support two earlier small observational studies. One in children, which reported lower oxidised low-density lipoprotein with HDF [ 26 ], and a second study based on 38 patients from Japan which reported that treatment with pre-dilution haemodiafiltration resulted in a higher mercapto-albumin to albumin ratio [ 27 ].However, not all studies have observed changes in oxidative stress, with one small study reporting varying results, with some lowering of total antioxidant capacity, but no change in superoxide dismutase [ 28 ]. Although slightly more HDF patients received were treated by thrice weekly schedules, haemodialysis treatments have themselves been reported to generate oxidative stress and generate peroxynitrite-induced oxidation of plasma lipids [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nakatani et al reported that age, anemia, and eGFR were significantly and independently associated with HNA in pre-dialysis CKD patients 15 . Studies reported that hemodialysis may remove uremic toxins and ameliorate the redox status of albumin by decreasing levels of HNA 30 , 31 . Therefore, patients who received routine dialysis or had severe renal function were also excluded from the present study.…”
Section: Discussionmentioning
confidence: 99%